The other histories of romanticism in the poetry of Percy Bysshe Shelley and Abdiilhak Hamid Tarhan - Çamoğlu, Arif Samet. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
Numerous scholarly definitions have been applied to Romanticism, each suggesting a specific set of criteria that can cover the term as broadly as possible in aesthetic, political, philosophical or historical concerns. One such attempt to come up with a binding understanding for it is the periodical criticism of Romanticism which is grounded on an appositional evaluation of the history of this literary phenomenon. Locating and explicating the temporal significance of Romanticism through the ways it departs from previous literary traditions, a certain wing of scholarship confines • Romanticism to a particular time of history, severing its ties with other ages. This thesis addresses and problematizes the periodical classification of Romanticism by investigating its relation with other centuries through the poetry of Percy Bysshe Shelley and Abdulhak Hamid Tarhan. Bringing these English and Ottoman Romantic poets together, this comparative study endeavors to expose the marriage of different discourses of different periods of history in their cited poems. While the use of the philosophical and scientific literatures of the Enlightenment in Shelley's verse necessitates the revision of the presumed break between the eighteenth and the nineteenth centuries, Tarhan's return to Sufism in his Romantic poetry challenges the pro-modem attitude prevalent in local Turkish scholarship. Exploring the characteristics of their Romantic poetics through a close reading of selected poems, the thesis argues that periodical definitions of Romanticism are in some cases anachronistic as proven by the Romanticisms of Shelley and Tarhan.
Keywords: Romanticism.